2019
DOI: 10.1021/acs.analchem.9b01914
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Proton Transport across Silica Nanochannel Membranes Investigated by Ion Conductance Measurements

Abstract: Proton transport plays an important role in many biological and technological processes. Numerous experiments and molecular dynamics simulations have proved the increase of proton mobility in confined nanostructures. In this work, we studied the proton transport across flow-through silica nanochannel membranes (SNMs) with vertically aligned channels, uniform diameter (∼2.3 nm), high porosity (16.7%), and ultrasmall thickness (88 nm). Taking into account both the mutual interaction between nanochannels and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Even for water molecules, a strong H-bond network was formed in a 10 nm cavity due to constrained geometry, which promoted intermolecular interactions (Figure f) . The confinement effect on binding behaviors will further cause several physical properties to deviate from the values measured in the bulk phase, such as dielectric constant, viscosity and molecular diffusivity. , For example, the viscosity of a poly­(ethylene oxide) melt confined by nanoscale channels showed more than 2 orders of magnitude greater viscosity than the bulk phase value . When confined in silica nanochannels, the transport of protons became anomalous with a rate that was at least four times greater than the theoretical value …”
Section: Unique Phenomena Under Nanoconfinementmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for water molecules, a strong H-bond network was formed in a 10 nm cavity due to constrained geometry, which promoted intermolecular interactions (Figure f) . The confinement effect on binding behaviors will further cause several physical properties to deviate from the values measured in the bulk phase, such as dielectric constant, viscosity and molecular diffusivity. , For example, the viscosity of a poly­(ethylene oxide) melt confined by nanoscale channels showed more than 2 orders of magnitude greater viscosity than the bulk phase value . When confined in silica nanochannels, the transport of protons became anomalous with a rate that was at least four times greater than the theoretical value …”
Section: Unique Phenomena Under Nanoconfinementmentioning
confidence: 99%
“…167 When confined in silica nanochannels, the transport of protons became anomalous with a rate that was at least four times greater than the theoretical value. 169 The enhanced noncovalent bonding of molecules under nanoconfinement can lead to local concentration enrichment. Combined with reduced mobility due to spatial restriction, as discussed above, this contributes to enhanced kinetics of chemical reactions.…”
Section: Nanoconfinementmentioning
confidence: 99%
“…Similar result was also observed previously, due to the mobility of H + in a nanochannel that can be ca. 4 times larger than its bulk value. Accordingly, we artificially raise the diffusivity of H + at pH 2 by a factor of 4 in the numerical simulation (Figure S6). This is helpful in exploring the contribution of H + diffusion, despite that the transport of H + can be more complicated in a nanoscaled confinement. Note that varying the ionic diffusivities will not influence qualitatively the ICR behavior of a conical nanopore …”
mentioning
confidence: 99%
“…This is consistent with the previous finding that the increase in the mobility of H + is more significant at a lower salt concentration. 45,47 However, whether there are other factors that might affect the transport of H + in confinements at a higher salt concentration deserves further study.…”
mentioning
confidence: 99%
“…[ 18 ] Bulk and surface charge behavior of mesoporous silica thin films was also reported by Zhao et al. [ 19 ] They showed that the measured conductance was at least four times higher than that calculated by theoretical models, indicating the effect of nanoconfinement on proton transport, as this was not considered in the calculations. To the best of our knowledge, studies explaining the pH‐dependent proton transport phenomena, not just those dependent upon proton concentration, of additional acid‐functionalized mesoporous silica have not yet been reported.…”
Section: Introductionmentioning
confidence: 62%